BIODIVERSITY OF REEF FISHES IN MARINE PROTECTED AREA OF KARIMUNJAWA NATIONAL PARK - Ernik Yuliana; Mennofatria Boer; Achmad Fahrudin; M. Mukhlis Kamal (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Karimunjawa National Park (KNP) has a high diversity of coral reef and fish. This study is aimed to analyze the biodiversity of reef fish in KNP. Field survey was conducted in KNP, District of Jepara, Central Java, in April-Juni 2015. Primary data was obtained by using survey and observation method,   includes the number of reef fish individuals per family, coral cover, turbidity, total nitrogen (N), and PO4. Secondary data were obtained from KNP authority. Belt transect method was used for counting the number of reef fish individuals, while coral cover was measured using line intercept transect (LIT) method. Abundance and biomass of reef fishes were analyzed descriptively, followed by cluster analysis. The results indicated that the average of coral cover in 2015 was 44.70%. The highest coral cover was in Taka Malang with 65.65% and the lowest was in Nirwana with 35.45%. The reef fish’s abundance in 2015 was dominated by Pomacentridae (60.46%) with an abundance of 14,850 no/ha, the second position was Caesionidae (11.77%) with an abundance of 2,892 no/ha, the third was Scaridae (6.27%) with an abundance of 1,540 no/ha. The highest biomass in 2015 was Scaridae (122.33 kg/ha), the second order was Caesionidae (104.91 kg/ha), and the third was Serranidae (50.80 kg/ha). Reef fish biodiversity in KNP is considering properly maintained, as demonstrated by high abundance and biomass of fish families.  Keywords: biodiversity, reef fish, Karimunjawa, marine protected area